Boredom, Apocalypse, and Beyond: Reading Havel through Patočka. Issue 2 (May 2018) - Krapfl, James
What is the power of the powerless today? By drawing on the philosophy of history that informed Havel's landmark essay, this piece presents notes for a possible sequel. It assesses the contemporary state of what Havel's mentor, Jan Patočka, called "technological civilization, " particularly with respect to the growing linkage Patočka perceived between boredom (a product of this civilization) and orgiastic violence. Reflecting on the Havelian panoramas of our time and the ideologies associated with them, the piece situates our present in the multimillennial Patočkan history of human beings' relation to meaning, violence, and responsibility. Following the logic behind Patočka's and Havel's Cassandra-like warnings from the 1970s, the piece concludes by confronting the increasing probability of global catastrophe, but it takes inspiration from their work to outline a program of responsible hope.